Improving Student Learning Using Picture Story Books in English - Aldo Aldo; Vidya Mandarani (Indonesian Journal Publisher, 2026)
Currently, English education really needs to use learning media such as picture story books and others to increase students’ enthusiasm for learning. Currently, English learning education must also have good learning tools for elementary school students, so that students’ learning abilities can improve well, teachers can use picture story book learning media as a teaching material so that students can develop learning patterns. This picture story book was created to attract students to want to learn English. This story book can be used by elementary school students to grade 7 middle school. This research also aims to improve student development in learning English.